A game theoretic framework for peer-to-peer market economy. (1st January 2011) - Okaie, Yutaka; Nakano, Tadashi
We consider a peer-to-peer resource market where participating peers provide their own computing resources to earn virtual money called energy, which is used in such a market to buy resources or services provided by others. Analogous to financial markets, a rapid increase or decrease of resource prices (e.g., high inflation or deflation) is not desirable, and it is important to maintain stable resource prices in peer-to-peer resource markets. In this paper, we develop a game theoretic framework for understanding the dynamics of resource prices where resource providing peers behave rationally; i.e., they determine prices for own resources to maximise their own energy gains. We then use the game theoretic framework to understand the market dynamics in two specific environments. In the first environment, all resource providing peers are fully connected by logical links and aware of the entire network topology. In the second environment, more realistic networks (e.g., small-world networks) are assumed where resource providing peers have a partial view about the network. Analytical and simulation studies are presented to identify conditions for peer-to-peer resource markets to achieve long-term price stability.